Closed Vs. Open Reduction/Salter Innominate Osteotomy for Developmental Hip Dislocation After Age 18 Months: Comparative Survival at 45-Year Follow-up. (5th August 2020) - Scott, Elizabeth J.; Dolan, Lori A.; Weinstein, Stuart L.
Abstract : Background: Despite widespread use of single-stage open reduction and pelvic osteotomy for treatment of developmental dysplasia of the hip (DDH) after walking age, this aggressive strategy remains controversial. We directly compared dislocated hips treated with closed reduction (CR) to those treated with open reduction and Salter innominate osteotomy (OR/IO) to estimate the relative hazard of total hip arthroplasty (THA) and the THA-free survival time. Methods: In a series of patients 18 to 60 months of age, 45 patients (58 hips) underwent CR and 58 patients (78 hips) were treated with OR/IO and followed to a minimum 40 years post-reduction. Observations in the survival analysis were censored if no THA had occurred by 48 years. Multivariate Cox regression analysis was used to estimate the hazard of THA given treatment, age, and bilaterality. Complications and additional procedures were noted. Results: At 48 years of follow-up, 29 (50%) of the hips survived after CR compared with 54 (69%) after OR/IO. At 45 years, the survival probability after OR/IO was 0.63 (95% confidence interval [CI] = 0.50 to 0.78) compared with 0.55 (95% CI = 0.43 to 0.72) after CR. The hazard ratio (HR) of THA was modeled as a function of treatment, age at reduction, and bilaterality. The effect of age and treatment on the outcome of hips in patients with unilateral involvement was minimal. However, age did significantly alter the relationship between treatment and outcome in bilateral cases. In the bilateral group, the predicted HR of THA was lower after CR in hips that were reduced at the age of 18 months (HR = 0.16, 95% CI = 0.04 to 0.64) but higher in those that were reduced at 36 months (HR = 4.23, 95% CI = 2.00 to 8.95). Additional procedures were indicated for 17% and 22% of hips after CR and OR/IO, respectively. Conclusions: Osteoarthritis and THA was more likely after CR than OR/IO, but the data do not indicate a difference in unadjusted hip-survival time. In patients with bilateral disease, an older age at reduction was associated with an increased hazard of THA after CR than after OR/IO. Both treatments provided substantial benefit relative to the natural history of DDH, but THA is the expected outcome in middle adulthood. Level of Evidence: Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.